Improving Employee Performance through Servant Leadership and Managerial Skills: The Strategic Role of Career Achievement - Benita Rachmania (Maneggio, 2026)
This study aims to analyze the influence of servant leadership and managerial skills on employee performance with career achievement as a mediating variable. The research uses a quantitative approach with the type of explanatory research. The data was analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the study show that servant leadership has a positive effect on employee performance and career achievement. Managerial skills have been proven to have a positive effect on career achievement, but do not have a direct effect on employee performance. Furthermore, career achievement has a positive and significant influence on employee performance. The results of the mediation test showed that career achievement was able to mediate the influence of servant leadership and managerial skills on employee performance. These findings indicate that service-oriented leadership and managerial skill development need to be integrated with career management systems to optimally improve employee performance. This research provides practical implications for human resource management in designing sustainable leadership and career development strategies